Schrodinger's Lamps!

Let k k and n n be positive integers with k = n + 10 k=n+10 . Let 2 n 2n lamps labelled 1 , 2 , 3... , 2 n 1,2,3...,2n be given, each of which can be either on or off. Initially all the lamps are off. We consider sequences of steps: at each step one of the lamps is switched (from on to off or from off to on).

Let N N be the number of such sequences consisting of k k steps and resulting in the state where lamps 1 1 through n n are all on, and lamps n + 1 n+1 through 2 n 2n are all off.

Let M M be number of such sequences consisting of k k steps, resulting in the state where lamps 1 1 through n n are all on, and lamps n + 1 n+1 through 2 n 2n are all off, but where none of the lamps n + 1 n+1 through 2 n 2n is ever switched on.

Find N M . \frac{N}{M}.


The answer is 1024.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Víctor Martín
Aug 12, 2014

For N N , we will have to make k k steps switching in each one the state of one of the 2 n 2n lamps. Thus, we will be able to make ( 2 n ) k { (2n) }^{ k } steps. How many of those final states are those we want? It's easy to say 2 2 n { 2 }^{ 2n } , but only half of the states are possible, since after m m steps, the sum of the states S S { S }_{ S } (taking 0 as a lamp switch off and 1 as a switched, or viceversa) will satisfy S S m ( m o d 2 ) { S }_{ S } \equiv m\quad (mod\quad 2) . So, the possible final solutions for N N are N = ( 2 n ) k 2 2 n 2 = ( 2 n ) k 2 2 n 1 N=\frac { { (2n) }^{ k } }{ \frac { { 2 }^{ 2n } }{ 2 } } =\frac { { (2n) }^{ k } }{ { 2 }^{ 2n-1 } } .

Same for M. The only difference in n is that we only switch the first n n lamps instead of the 2 n 2n lamps. So, the possible final solutions for M M will be M = n k 2 n 2 = ( n ) k 2 n 1 M=\frac { { n }^{ k } }{ \frac { { 2 }^{ n } }{ 2 } } =\frac { { (n) }^{ k } }{ { 2 }^{ n-1 } } .

Then N M = ( 2 n ) k 2 2 n 1 n k 2 n 1 = ( 2 n n ) k 2 n 1 2 2 n 1 = 2 k 2 n 1 2 n + 1 = 2 k n \frac { N }{ M } =\frac { \frac { { (2n) }^{ k } }{ { 2 }^{ 2n-1 } } }{ \frac { n^{ k } }{ { 2 }^{ n-1 } } } ={ \left( \frac { 2n }{ n } \right) }^{ k }·\frac { { 2 }^{ n-1 } }{ { 2 }^{ 2n-1 } } ={ 2 }^{ k }·{ 2 }^{ n-1-2n+1 }={ 2 }^{ k-n }

Taking k = n + a k=n+a (yes, a = 10 a=10 ): 2 k n = 2 n + a n = 2 a { 2 }^{ k-n }={ 2 }^{ n+a-n }={ 2 }^{ a } .

As a = 10 a=10 , the solution will be 2 a = 2 10 = 1024 { 2 }^{ a }={ 2 }^{ 10 }=\boxed { 1024 }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...